2013
DOI: 10.1103/physreve.88.022314
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of local relaxation events in an aging three-dimensional glass: Spatiotemporal correlation and dynamical heterogeneity

Abstract: We investigate the spatiotemporal distribution of microscopic relaxation events, defined through particle hops, in a model polymer glass using molecular dynamics simulations. We introduce an efficient algorithm to directly identify hops during the simulation, which allows the creation of a map of relaxation events for the whole system. Based on this map, we present density-density correlations between hops and directly extract correlation scales. These scales define collaboratively rearranging groups of partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…6 and 7 respectively. Similar to previous results in fragile glass formers [13,20,21,[23][24][25] χ α max and t α max increase with increasing t w . It is possible that χ α max reaches a plateau for large t w , but the noise in the results is too large to allow for any definite conclusions to be drawn.…”
supporting
confidence: 91%
“…6 and 7 respectively. Similar to previous results in fragile glass formers [13,20,21,[23][24][25] χ α max and t α max increase with increasing t w . It is possible that χ α max reaches a plateau for large t w , but the noise in the results is too large to allow for any definite conclusions to be drawn.…”
supporting
confidence: 91%
“…As expected, polymer chain ends are more mobile; however, the mobility does not necessarily propagate along the backbone of the chains [8]. More recently, the spatiotemporal distribution of monomer hopping events was investigated in an aging polymer glass quenched below the glass transition temperature [9].…”
Section: Introductionmentioning
confidence: 79%
“…It was shown that before merging into a single dominating cluster, the volume distribution of clusters of hopping monomers follows a power-law decay with an exponent of two, and the clusters have slightly noncompact shapes [9].…”
Section: Introductionmentioning
confidence: 99%
“…-simple numerical glass models like Lennard-Jones glasses (Falk and Langer, 1998;Maloney and Lemaître, 2004;Maloney and Lemaître, 2006;Tanguy et al, 2006) and other systems (Gartner and Lerner, 2016), -numerical models of metallic glasses (Rodney and Schuh, 2009;Srolovitz et al, 1983), -numerical models of silicon glasses (amorphous silicon) (Albaret et al, 2016;Fusco et al, 2014), -numerical models of polymer glasses (Papakonstantopoulos et al, 2008;Smessaert and Rottler, 2013) -dense colloidal suspensions (Chikkadi and Schall, 2012;Jensen et al, 2014;Schall et al, 2007), -concentrated emulsions (Desmond and Weeks, 2015), -dry and wet foams (Biance et al, 2009(Biance et al, , 2011Debregeas et al, 2001;Kabla and Debrégeas, 2003), -granular matter (Amon et al, 2012(Amon et al, , 2013Denisov et al, 2016;Le Bouil et al, 2014).…”
Section: Evidencementioning
confidence: 99%